Potential distribution and abundance of candelilla (Euphorbia antisyphilitica) in northern Zacatecas, Mexico - Bañuelos-Revilla, José Enrique; Palacio-Núñez, Jorge; Martínez-Montoya, Juan Felipe; Olmos-Oropeza, Genaro; Flores-Cano, Jorge Alberto (Instituto de Ecología, A.C., 2019)
The candelilla (Euphorbia antisyphilitica) grows in arid regions of Mexico, having social and economic importance, although its availability is not clearly defined. The objective of the study was to estimate their potential distribution and abundance in the north of Zacatecas state. A potential distribution modeling was performed through MaxEnt® using 18 data of presence, 8 historical and 10 current, and 27 predictive variables. The presence was corroborated in the field by means of 29 random points within the area of potential distribution, and 19 others outside it. The population density was estimated with plots, measuring the size of the individuals, and considering the following variables: vegetation and soil type, altitude, and slope. A Kruskal-Wallis test was used. The model generated an accurate prediction (AUC = 0.920), in which 11 variables contributed with 82.1% to the potential distribution, the most important being: vegetation type, exposure, slope, altitude, and vegetation cover. The potential distribution area was 19.2% of the total study area, with a population density of 295 767.3 individuals per square kilometer. This was significantly influenced by the vegetation type and altitude, while the slope affected the plant height. There were positive presence results in 37.9% of the validation sites with potential distribution in the study area, plus 10.5% outside of the potential distribution area. It is concluded that by using the MaxEnt® algorithm the potential distribution of wild plants, such as candelilla, can be modeled; the potential distribution was discontinuous and less than 20%.